Arsenic bioaccumulation in fish of the lower meghna river: Seasonal dynamics, species sensitivity, and public health implications - Shyamal Kumar Paul; Nusrat Jahan; Debasish Saha; Bhakta Supratim Sarker; Priyanka Rani Majumdar; Moshiur Rahman (PLoS ONE, 2025)
The Lower Meghna River (LMR), located in one of Bangladesh’s most arsenic-contaminated regions, is essential for local fisheries and provides water for drinking, irrigation, and daily use. Consequently, this study investigates arsenic accumulation in ten edible, small indigenous species (SIS) of fish, considering their morphology, habitats, diets, and water and sediment conditions. Samples were analysed across three distinct river segments during three seasons. The arsenic levels in water and sediment fell within non-polluting limits; however, certain fish species, including Mystus vittatus, Glossogobius giuris, Lepidocephalichthys guntea, Neotropius atherinoides, and Apocryptes bato, surpassed the WHO’s safe consumption threshold (1 mg/kg). Arsenic levels in water, sediment, and fish show significant seasonal variations (p < 0.05) but no notable spatial differences (p > 0.05). Strong correlations exist between arsenic in fish and both water and sediment (R2 > 0.5). Fish body shape and the presence of scales notably influence arsenic accumulation. Benthic carnivores accumulate more arsenic than pelagic and benthic-pelagic omnivores. Children are especially vulnerable to health risks. While Hazard Indices (HI) and Hazard Quotients (HQ) for water and sediment remain within safe limits, fish consumption presents a risk. Furthermore, the cancer risk associated with fish consumption is higher than that from water and sediment pathways. These results highlight a significant food safety concern and emphasize the need for integrated arsenic risk management strategies in the Lower Meghna River region.